Development and initial validation of an instrument to measure novice nurses' perceived ability to provide care in acute situations - PCAS - Anders Sterner; Emma Säfström; Lina Palmér; Nerrolyn Ramstrand; Magnus Andersson Hagiwara (BMC, 2020)
Abstract Background Novice nurses need to be better prepared to provide care in acute situations. There is currently no validated scale specifically measuring nurses' perception of their ability to provide care in acute situations. The aim of this study was to develop and examine the psychometric properties of a scale that measures novice nurses self-reported perception of ability to provide care in acute situations. Method Development and test of the psychometric properties of the Perception to Care in Acute Situations (PCAS) scale. Items were generated from interviews with novice nurses (n = 17) and validated using opinions of an expert panel and cognitive interviews with the target group. Two hundred nine novice nurses tested the final scale. Exploratory factor analysis (EFA) was used to test construct validity, item reduction and underlying dimensions between the measured variables and the latent construct. Result The PCAS scale contains 17 items grouped into three factors. EFA demonstrated a clean three factor logic construct solution with no cross-loadings, high correlation for the total scale in both Cronbach's alfa 0.90 and ordinal alpha 0.92. Conclusions The PCAS scale has proven to have acceptable validity. The factors," confidence in provision of care", "communication" and "patient perspective" are likely to be important aspects of providing care in acute situations. Additional testing of the PCAS is needed to conclude if it is sensitive enough to evaluate interventions aimed at improving novice nurses competence and suitable as a guide for reflection for novice nurses.